An Intuitionistic Fuzzy Sets Implementation for Key Distribution in Hybrid Message Encryption Over Wsns - Y .M. Wazery; Mona A. S. Ali (Institute of Advanced Engineering and Science, 2018)
WSN is a way of handling dangerous and hostile environments safely. It replaces human existence with nodes and units that could sustain its existence under extreme circumstances. The significance of WSN arises from the importance of the data gathered through its nodes. Due to the fact of WSN that it is open air environment, security issues must be considered, for example authentication of new units and the encryption of data transmitted between these units. This research provides a new model covering two important aspects in WSN. The first aspect is the creation of the key that will be used for the current session between a pair of nodes. In this step the research introduces the intuitionistic fuzzy sets to handle the WSN criteria simultaneously and efficiently, in order to decide the exact key length required depending on the status of the network parameters. The second aspect is the distribution of the key between the units desiring communications. This phase starts by authenticating each entity to each other and to the cluster head, then one unit suggests a key and the other one confirms. It then starts communication using that key. This phase shows the hybrid cryptography applied in which the algorithm uses asymmetric encryption for authentication then uses symmetric encryption to secure the connection between the two units. Experimental results in this research could categorized also into two classes. The first class is key size model in which the proposed model compared to ordinary KNN and fuzzy model related to the determination of the key size. The proposed model shows an overall efficient way relating to decide the key size. The second class of experiments is to distribute the intermediate key efficiently; at this point the proposed model shows resilience and efficiency compared to distributing the key directly through cluster head.